BSAVA manual of canine and feline gastroenterology - Hall, E. J. (Ed J.); Williams, David A.; Kathrani, Aarti (BSAVA manual series., 2020)
"The busy small animal practitioner is likely to see a dog or cat with GI signs most days and this manual provides a logical approach to GI problems and their solutions. Our understanding of the digestive and immunological functions of the GI tract has expanded exponentially in recent years and this third edition reflects these developments. The manual is divided into sections covering diagnostic procedures and techniques; diagnostic approaches to problems; patient management; and diseases of specific systems and organs"--Publisher's description